Analysis of influences of socio-demographic factors on the personality structure of non-homicide offenders of prison Foča - Dragan Jovanović; Snežana Medenica; Novica Petrović; Aleksandra Salamadić (Биомедицинска истраживања, 2013)
Introduction: . Up-to-now researches have shown that there is a connection between the structure of per sonality and possible criminal behaviour, and that the structure of personality is formed in the co-action of biological, psychological and social factors. The aim of this paper is to conduct analysis of influences of socio-demographic factors on the structure of the personality of non-homicide offenders (prisoners who did not commit homicide): the age of a prisoner, qualifications, nationality, number of children in the prisoner’s family, the order of births, qualifications and jobs of prisoner’s parents, housing- whether he owns a house or a flat, or whether he is a tenant or lives in abandoned property, participation in war, death of close persons (family members, friends), close persons wounding (family members, friends), being present when someone died or he was wounded, the change of residence because of war, having chronic patients in the family, alcoholism and drug addiction in the family, smoking, alcohol consump tion and the prisoner’s employment. Methods: . The study is controlled, transversal (the cross section study) which includes the prisoners of the Penal Institution Foca, who did not commit homicide - 72 prisoners. Control group consists of 60 persons who show signs of agression in socially accepted activities- members of the Hunting Association Foca. For the purpose of the basic problem exploration and the aims of the research the Questionnaire of general data was used. Results: . The features of the non-homicidal offenders are influenced by the age of the prisoner, qualifications of the prisoner, qualifications and jobs of the prisoner’s parents, housing, war stressors (participation in war, the loss and wounding of a closed person, being present when someone died or he was wounded, change of residence because of war), alcoholism and drug addiction in the family, alcohol consumption and the prisoner’s employment, having chronic patients in the family and smoking. Nationality, number of children in the prisoner’s family, the order of births, do not have any influence. Conclusion: . Socio-economic factors influence the personality features of the prisoner more than demo graphic factors.
Keywords: socio-demographic factors; personality structure; non-homicidal offenders